Culture, religion, and homonegativity: a multi-level analysis - Leach, Erica (Mental health, religion & culture, 2022)
The purpose of this study was to connect possible factors that may influence homonegativity within an individual. Specifically, we hypothesised that societal threats and individual values of tightness would positively predict the orthodox, intrinsic, and extrinsic orientations, and they would negatively predict the quest and secular orientations. We also hypothesised that orthodox, intrinsic, and extrinsic orientations would in turn positively predict homonegativity, whereas quest and secular orientations would negatively predict homonegativity. Participants (n = 472) completed an online survey of societal threats, tightness, religious orientation, and homonegativity. The results showed how societal and perceived threats in hometown areas may predict one’s religious orientation. The results also showed how one’s religious orientation may influence an individual’s level of homonegativity.